Study of Regenerated Plants Aspen from Callus - G. A. PETROVA; E. A. KALASHNIKOVA (International Journal of Secondary Metabolite)
This article presents the results of an experiment for obtaining healthy seed aspen by micropropagation. The studies we have obtained from callus tissue regenerated plants aspen, various different growth rate. Were obtained two types of plants: plants, characterized by rapid growth and plants, which are characterized by slow growth. The data of biochemical studies on the content of soluble phenolic compounds in plants regenerated aspen. So plants with rapid growth during the five passages, the total content of soluble phenolic compounds were at 30-33 mg / g wet weight, and in plants with slow growth in this account of the indicators increased significantly and amounted to 52-58 mg / g wet weight . In addition, the results of cytological studies of regenerated plants aspen derived from callus tissue, which resulted in the observed changes in the level of the number of chloroplasts in the guard cells of stomata. Necessity of breeding plants regenerated aspen characterized by rapid growth and their introduction in forestry production in the Republic of Tatarstan.